2006
DOI: 10.1111/j.1440-1819.2006.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of partial seizures with gabapentin: Double‐blind, placebo‐controlled, parallel‐group study*

Abstract: This double-blind study was conducted to evaluate the efficacy and safety of gabapentin 1200 mg/ day and 1800 mg/day (t.i.d.) compared to placebo as an adjunctive therapy in patients with refractory epilepsy. Patients were included when they had partial seizures at least eight times during a 12-week baseline period despite treatment with one to two antiepileptic drugs. After baseline, eligible patients were randomized to gabapentin 1200 mg/day, 1800 mg/day, or placebo for 12-week treatment. The primary end-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…On the other hand, some studies suggested that GABAergic neurons are selectively spared following some other insults (Mathern et al, 1995; Tecoma et al, 1989). Nevertheless, the fact that epilepsy may be treated using drugs that enhance GABA receptor mediated inhibition (Fueta et al, 2005; Yamauchi et al, 2006) and that seizures can be triggered with GABA receptor blockers, such as penicillin and bicuculline (Karlsson et al, 1992), suggests that altered inhibition might represent an important pathogenetic mechanism of chronic epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies suggested that GABAergic neurons are selectively spared following some other insults (Mathern et al, 1995; Tecoma et al, 1989). Nevertheless, the fact that epilepsy may be treated using drugs that enhance GABA receptor mediated inhibition (Fueta et al, 2005; Yamauchi et al, 2006) and that seizures can be triggered with GABA receptor blockers, such as penicillin and bicuculline (Karlsson et al, 1992), suggests that altered inhibition might represent an important pathogenetic mechanism of chronic epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several doubleblind studies of new AEDs have been published. [7][8][9][10][11][12][13][14] As far as we know, these studies have not been included in the previous meta-analyses in which adverse effects have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were recruited from 6 Japanese hospitals and selected according to the following criteria: (1) between 3 months and 18 years old, (2) seizures refractory to at least 2 first-line antiepileptic drugs, (3) at least 4 seizures a month during the 3 months before ethyl loflazepate administration, and (4) at least 24 months of follow-up.…”
Section: Methodsmentioning
confidence: 99%